Essays on immigration and homeownership - Hussain, Arsalan (My University, 2026)
This dissertation consists of three essays. The first essay examines how European immigrants to the United States between 1900 and 1930 assimilated through homeownership, a key marker of economic stability, integration, and convergence with native living standards. Using the Multigenerational Longitudinal Panel (MLP) data, I track individual households over time to account for return migration and focus on genuine gains in ownership. Cohort level and age–cohort–period regressions show that immigrant cohorts began with substantial homeownership gaps relative to natives but made steady gains, averaging an increase of 8.1 percentage points per decade. Younger arrivals generally start with smaller gaps and close a larger share of their initial disadvantage, while regional differences among European immigrants converge to native rates by 1930. Ethnic enclave analysis shows that higher city-level concentrations of co-ethnics increase homeownership, whereas higher neighborhood-level concentrations reduce it. Panel-based transition analysis reveals that immigrants are more likely to enter and less likely to exit homeownership than natives, with these dynamics explaining part of the observed convergence, highlighting the multifaceted process of immigrant assimilation. The second essay examines the effects of immigration shocks on native homeownership in the United States during the early twentieth century. Using full-count and linked U.S. Census data from IPUMS, together with a shift-share instrument for immigrant inflows, we examine how changes in city-level immigrant populations affect native homeownership and transitions into and out of homeownership. We find that a 5-percentage point increase in the fraction of a city’s population made up of recent immigrants raises native homeownership rates by 2.28 percentage points, while a 5-percentage point increase in the change in the immigrant share increases the probability that natives transition into homeownership by 9.82 percentage points and reduces transitions out of homeownership by 4.59 percentage points. We find suggestive evidence that immigration lowered home prices at the city level, while the estimates for rents are statistically insignificant. Together, these findings are consistent with housing costs being one possible channel through which immigration affects native housing outcomes. We also find that immigration increases household formation among natives, raising the probability that an individual who was not a household head in one census becomes a household head in the next. Newly formed households are also more likely to enter homeownership when immigration increases. Some of our results may reflect preexisting city characteristics correlated with immigration, raising concerns about the validity of the instrument in those specifications. The third essay examines the impact of the legalization provisions of the Immigration Reform and Control Act (IRCA) of 1986 on U.S. housing markets. Using quarterly national data on immigration flows, housing demand, prices, and supply, we estimate Bayesian Structural VAR models identified using sign and narrative sign restrictions to recover the causal effects of IRCA-induced immigration shocks. We find that the legalization shock generated a persistent increase in immigration, leading to heterogeneous adjustments across housing markets. Rental markets adjust primarily through quantities, with sharp declines in vacancy rates and only modest increases in rents. In contrast, owner-occupied markets exhibit stronger responses along both quantity and price margins, including declines in vacancies, increases in single-family home sales, and sustained appreciation in house prices. Despite these demand pressures, we find little evidence of a meaningful supply response through housing permits or starts. Overall, legalization-induced immigration generated persistent housing market pressures, with adjustment occurring mainly through tighter market conditions and rising prices rather than supply expansion.
Keywords: Homeownership; Immigration; Assimilation; Linked census; Immigration Reform and Control Act (1986); Housing Market